Not just a climate problem: the safety and health risks of methane super-emitter events - Sofia Bisogno; Chowdhury G Moniruzzaman; Nick Heath; Christos Efstathiou; Jeremy K Domen; Lee Ann L Hill; Jasmine Lee; Drew R Michanowicz; Quintin Munoz; Yanelli Nunez; Sebastian T Rowland; Daniel Bon; et al. (Environmental Research Letters)
Methane super-emitter events (>100 kg methane hr ^−1 ) are prevalent across the oil and gas supply chain and are being targeted for methane mitigation policies due to their climate impacts; however, few studies have evaluated the air quality impacts and direct safety and public health risks. Here, we evaluate seven upstream oil and gas methane super-emitter events to examine the safety (explosivity) risks from methane and the short-term, noncancer health risks from benzene and other key co-emitted non-methane volatile organic compounds (NMVOCs). We used airborne instrument and satellite-measured methane emissions rates to estimate hourly air concentrations of methane using US EPA’s American Meteorological Society/Environmental Protection Agency Regulatory Model (AERMOD), a regulatory-grade dispersion model, and applied estimated speciated NMVOC-methane molar ratios to calculate hourly air concentrations of NMVOCs. We assessed when and where hourly modeled methane and NMVOC air concentrations exceeded national safety (0.5% methane) and state-based health (8 ppb and 53 ppb benzene) benchmarks. Large methane super-emitters (>2900 kg hr ^−1 ) had safety benchmark exceedances as far as 270 m from the source, indicating that safety risks are greatest for facility workers and nearby communities. Health benchmark exceedances were the greatest and most frequent close to the source (<300 m), but, in contrast to the safety risks, reached beyond one kilometer (1.1–19 km) for modeled methane super-emitters (210–15 800 kg hr ^−1 ), posing health risks to residents and sensitive populations. We also found that smaller methane super-emitters may pose outsized health risks: our second lowest methane emission case (539 kg hr ^−1 ) yielded the highest benzene air concentration (28 000 ppb), farthest 8 ppb benzene exceedance distance (19 km), and highest frequency of health benchmark exceedances between 1–5 km (2.6%). Our study demonstrates that policies and early detection efforts that control methane super-emitters should prioritize factors beyond methane emissions rate magnitude, such as gas composition, to provide the strongest co-benefits for public health and safety.